CHEMOTHERAPY-INDUCED CARDIAC TOXICITY AND HEART FAILURE - Bayramzade, S.R.; Mehdiyeva, N.I.; Bakhshiyev, M.M. (World of Medicine and Biology, 2024)
Over the past 20 years, advancements in cancer treatments have contributed to a consistent decline in cancer-related mortality, paralleled by an increase in cancer survivorship. As survivorship rises, treatment-related side effects, particularly cardiovascular toxicities associated with cancer therapies, have gained prominence due to their significant impact on patient outcomes. Effective management of cardiovascular toxicities is critical, as it influences the choice of anticancer therapies and affects long-term morbidity and mortality among cancer patients. Despite significant advancements in anti-cancer therapies that have improved patient survival, these treatments are often accompanied by an increased risk of treatment-related morbidity and mortality, particularly from cardiovascular diseases. Cardio-oncology, the multidisciplinary field, has gained considerable attention in recent years. However, further research is required to explore the complex mechanisms of chemotherapy-induced cardiovascular toxicity. This review includes recent information and evidence related to assessing the cardiotoxicity of chemotherapy and the ways of managing this problem.
Keywords: chemotherapy; cardiotoxicity; myocardial dysfunction